(untitled) (Applied Biological Research, 2012)
A number of experiments were conducted to know the optimum size, shape and concentration of nanoparticles to be sprayed to plants for better penetration and translocation. Nanoparticles were capable of penetrating living plant tissues when sprayed on plant leaves, and migrated from leaves to different parts of plant. The results demonstrated 14.7% nanoparticles loss when sprayed by aerosol technique (using nebulizer) as compared to 32.5% loss by normal sprayer. Low concentration (< 5 ppm) of nanoparticles were better absorbed and translocated through plant leaves. Higher the particle size lower was nanoparticle penetration. Particle size <20 nm may be preferred to spray. Nanocube proved better shape to be sprayed to plants.